2008
DOI: 10.1016/j.tins.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

White matter in learning, cognition and psychiatric disorders

Abstract: White matter is the brain region underlying the gray matter cortex, composed of neuronal fibers coated with electrical insulation called myelin. Previously of interest in demyelinating diseases such as multiple sclerosis, myelin is attracting new interest as an unexpected contributor to a wide range of psychiatric disorders, including depression and schizophrenia. This is stimulating research into myelin involvement in normal cognitive function, learning and IQ. Myelination continues for decades in the human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
991
2
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,117 publications
(1,021 citation statements)
references
References 103 publications
(117 reference statements)
17
991
2
11
Order By: Relevance
“…Is WM involved in synchronisation? The excellent review by Fields (2008) might answer this question. Fields (2008) points out that WM has been traditionally considered a passive insulation substance that ensures the transmission of neural impulses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is WM involved in synchronisation? The excellent review by Fields (2008) might answer this question. Fields (2008) points out that WM has been traditionally considered a passive insulation substance that ensures the transmission of neural impulses.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent review by Fields (2008) might answer this question. Fields (2008) points out that WM has been traditionally considered a passive insulation substance that ensures the transmission of neural impulses. The author proposes that emerging evidence indicates this is a too simplistic perspective, and WM also participates in the speed control of impulse conduction and consequently in the synchronisation among cortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Myelination does not simply maximize speed of transmission, it fine-tunes the timing and synchrony of neuronal firing patterns (Fields and Stevens-Graham, 2002). Myelin also influences neuronal plasticity by releasing molecular factors that inhibit axon sprouting and the creation of new synapses (Fields, 2008). These non-subtle impacts of myelin on the brain's ability to process information and adapt to the environment may underlie many of the cognitive abilities associated with our species.…”
Section: White Mattermentioning
confidence: 99%
“…Measures of myelination and white matter integrity have been shown to be reflected in the efficiency (Deary et al, 2006;Engel, Fries, & Singer, 2001;Li et al, 2009) and the speed (Gutiérrez, Boison, Heinemann, & Stoffel, 1995;Madden, Bennett, & Song, 2009;Penke et al, 2010;Tolhurst & Lewis, 1992;Waxman, 1980) of information processing, with such factors shown to modulate performance on a range of cognitive tasks (Deary et al, 2006;Li et al, 2009;Turken et al, 2008). Critically, myelination has been shown to be modifiable by experience (see Fields, 2008) and to increase as a result of learning (Bengtsson et al, 2005) and therefore has the potential for modulation by environmental variables such as exposure to literacy training. Studies have indeed shown that myelination of brain regions associated with language processing coincides with vocabulary acquisition (Pujol et al, 2006).…”
Section: Cognitive Efficiency and Literacymentioning
confidence: 99%